“And the walls came a-tumblin’ down…” | Comment recréer l’ambiance propre au séminaire dans un cours en ligne? - Thomas Michael Power (Canadian Journal of Learning and Technology, 2015)
This case deals with a university program which is well respected but requires changes to be made to it as enrollments dwindle. Pressure from administration is making the Program Head and Program Committee members as well as Senior Instructional Designer LeFort consider new options for its delivery. Online learning is not a well-established practice among regular faculty although lecturers in the program are open to it. LeFort has to find a solution that maintains quality of instruction while increasing accessibility and enhancing cost-efficiency.